1999
DOI: 10.1007/s002280050609
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and medication knowledge among elderly Japanese home-care recipients

Abstract: In this study, compliance among elderly Japanese home-care recipients was found to be associated with receiving pharmacist counseling, frequency of meals, and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
3
17

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 16 publications
1
42
3
17
Order By: Relevance
“…They are also more vulnerable as a consequence of diminished plasticity due to their advanced age. According to a study by Okuno et al, 25% of the elderly aged 80 years and over do not take their medicines as prescribed [1]. Age is the strongest predictor of a higher number of medicines.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They are also more vulnerable as a consequence of diminished plasticity due to their advanced age. According to a study by Okuno et al, 25% of the elderly aged 80 years and over do not take their medicines as prescribed [1]. Age is the strongest predictor of a higher number of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Most scientists think that more medicines lead to poorer compliance [2][3][4]. However there are studies that have contradicted this connection [1,5] or even found the opposite [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A maioria dos idosos utiliza mais de um medicamento periodicamente e quando hospitalizados recebem entre oito a quinze, representando um consumo de aproximadamente 30 a 35% de todos os medicamentos prescritos nos Estados Unidos (Baum et al, 1984;Ostrom et al, 1985;Piraino, 1995;Salom & Davis, 1995). No Japão, em 1995, a população com 65 anos ou mais era de 14,5%, com consumo de 30,6% de todos os medicamentos prescritos (Okuno et al, 1999). Já na Inglaterra, em 1985, os idosos receberam 39% de todas as prescrições de medicamentos (Cartwright & Smith, 1988).…”
unclassified